A Typical Immune T/B Subset Profile Characterizes Bicuspid Aortic Valve: In an Old Status?. (5th April 2018) - Balistreri, Carmela R.; Buffa, Silvio; Allegra, Alberto; Pisano, Calogera; Ruvolo, Giovanni; Colonna-Romano, Giuseppina; Lio, Domenico; Mazzesi, Giuseppe; Schiavon, Sonia; Greco, Ernesto; Palmerio, Silvia; Sciarretta, Sebastiano; et al.
Abstract : Bicuspid valve disease is associated with the development of thoracic aortic aneurysm. The molecular mechanisms underlying this association still need to be clarified. Here, we evaluated the circulating levels of T and B lymphocyte subsets associated with the development of vascular diseases in patients with bicuspid aortic valve or tricuspid aortic valve with and without thoracic aortic aneurysm. We unveiled that the circulating levels of the MAIT, CD4+IL−17A+, and NKT T cell subsets were significantly reduced in bicuspid valve disease cases, when compared to tricuspid aortic valve cases in either the presence or the absence of thoracic aortic aneurysm. Among patients with tricuspid aortic valve, these cells were higher in those also affected by thoracic aortic aneurysm. Similar data were obtained by examining CD19+ B cells, naïve B cells (IgD+CD27−), memory unswitched B cells (IgD+CD27+), memory switched B cells (IgD−CD27+), and double-negative B cells (DN) (IgD−CD27−). These cells resulted to be lower in subjects with bicuspid valve disease with respect to patients with tricuspid aortic valve. In whole, our data indicate that patients with bicuspid valve disease show a quantitative reduction of T and B lymphocyte cell subsets. Future studies are encouraged to understand the molecular mechanisms underlying this observation and its pathophysiological significance.